Ion exchange for halide perovskite: From nanocrystal to bulk materials - Haotian Jiang; Siqi Cui; Yu Chen; Haizheng Zhong (Nano Select, 2021)
Abstract Halide perovskite, an ionic semiconductor, with the typically structural composition of ABX3 has become the extremely popular star in optoelectronics due to its superior photophysical properties and easily solution processing. In comparison with the traditional semiconductors, the perovskite possesses a low crystal formation energy with facile solution synthesis, which results into its soft and dynamic crystal lattice. Therefore, the post‐synthetic composition tuning via ion exchange has been proved to be an effective technique to introduce heteroatoms into perovskite lattice. In this review, we summarize the recent progress on ion exchange of halide perovskites, including mechanisms, methods, as well as different scales from low‐dimensional nanoscale to bulk crystal. Besides, we also briefly discuss the prospective of ion exchange for halide perovskites, and hope it benefit for the structural design and compositional optimization in halide perovskites for various optoelectronic applications.